Field reports form for submitting seasonal observations of Iowa birds, Mark Proescholdt, fall 1994 - Proescholdt, Market al (1994)
An annotated list of birds sighted by Mark Proescholdt and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1994. Plustek - flatbed